Study of recycling of carbon tailings from Portland cement pro-duction - Mendes Bernal, Arlindo; Messias Soares, Mariana; Gustavo Mendes de Jesus, Leandro (International Journal of Scientific World, 2023)
In the clinker Portland production process, rotary kilns burn fuels to reach temperatures as high as 1450 °C. In the Mato Grosso do Sul State, the most common fuel used in such kilns is grounded charcoal. After the grinding steps, charcoal is sieved, and the re-tained material is discarded as tailings. Despite such materials have some carbon matter in its composition, it is a high ash content material. This work is based on the hypothesis that, during the grinding of the material, organic compounds would break in finer particles since they show lower abrasive strength. Thus, ash materials would remain in the coarser particles. The goal of the work is to evaluate the viability of the use of charcoal fines in Portland cement to reuse the material in clinker Portland production. To achieve the proposed goal, fines were fractionated in different particle sizes. Each size fraction was characterized regarding its ash content, proximate analysis, and calorific value. The results allowed to relate size fraction with ash content and calorific value. The results revealed that coarser size fractions (retained in 0,500 mm) presented lower ash content and calorific value. Furthermore, such size fractions correspond to 24,04 % in mass of material.